2019
DOI: 10.1200/jco.2019.37.15_suppl.10014
|View full text |Cite
|
Sign up to set email alerts
|

Randomized use of anti-GD2 antibody dinutuximab beta (DB) long-term infusion with and without subcutaneous interleukin-2 (scIL-2) in high-risk neuroblastoma patients with relapsed and refractory disease: Results from the SIOPEN LTI-trial.

Abstract: 10014 Background: We determined the role of scIL-2 combined with long term infusion (LTI) of DB in patients (pts) with high-risk relapsed/refractory neuroblastoma. Methods: 160 pts were enrolled into an open label SIOPEN Phase II clinical trial (EudraCT 2009-018077-31). Pts were randomly assigned to receive up to 5 cycles of 100 mg/m2 DB-LTI (d8-17) and 160 mg/m2 oral isotretinoin (d19-32) (81 pts) with and without 6x106IU/m2 scIL-2 (d1-5; 8-12) (79 pts). Endpoints were toxicity, response rates and 2yrs-event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Dinutuximab was approved for the treatment of high-risk neuroblastoma in the setting of minimal residual disease (42) and recently in neuroblastoma patients with refractory/resistant disease (43). However, dinutuximab is associated with doselimiting neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Dinutuximab was approved for the treatment of high-risk neuroblastoma in the setting of minimal residual disease (42) and recently in neuroblastoma patients with refractory/resistant disease (43). However, dinutuximab is associated with doselimiting neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Despite therapeutic advances, HRNB has a poor prognosis. Clinical trials led by the SIOPEN group have shown that immunotherapy with dinutuximab beta as part of multimodal treatment improves survival in patients with HRNB [ 8 , 9 , 12 , 13 ]. However, published literature on the use of this therapy in real-world settings is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the positive results of the SIOPEN trials [ 8 , 12 , 13 ], dinutuximab beta was approved in Europe in May 2017 for the treatment of HRNB in patients ≥12 months of age who have achieved at least a partial response to induction chemotherapy, followed by MAT and ASCT, and in patients with a history of relapsed or refractory neuroblastoma with or without residual disease [ 14 ]. Five cycles of dinutuximab beta should be administered either as continuous infusion for the first 10 days of each 35-day cycle (10 mg/m 2 per day; cumulative dose 100 mg/m 2 ) or as short 8-h infusion for the first 5 days of the cycle (20 mg/m 2 per day; cumulative dose 100 mg/m 2 ) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an on-target effect, pain, including neuropathic pain, is commonly experienced in children treated with dinutuximab beta [10][11][12]15]. GD2, the target of dinutuximab beta, is not only expressed on the surface of NB cells but also in normal human tissue in the central and peripheral nervous system [16].…”
Section: Painmentioning
confidence: 99%
“…Due to the immunotoxic effects of monoclonal antibodies [ 18 ], hypersensitivity reactions are an expected AE in patients receiving dinutuximab beta [ 10 , 11 , 15 ]. Hypersensitivity reactions may include mild symptoms (e.g.…”
Section: Optimising Supportive Care For Children Receiving Dinutuximab Betamentioning
confidence: 99%